(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
IoT technology is drawing a very important communication line between individuals. It’s providing how of effective communication. Additionally to the current, it’s conjointly creating people’s life higher by providing how for good home systems, good agriculture systems and even additional good systems that folks want. The maximum amount as this technology is sweet as attackers attempt to exploit it during a unhealthy thanks to attack the IoT systems and build edges of innocent sensitive knowledge and data. This makes it necessary to develop ways and techniques that might defend IoT systems. That successively defend people’s sensitive info. Security and privacy of IoT systems became a challenge and a very important a part of IoT systems. Security and privacy problems take issue in their danger level. Some attacks are additional dangerous than different attacks. Also, attacks take issue in their supply some attacks are internal and different attacks are external. Attacks may be completely different however their negative have an effect on is that the same and vary within the dangerous level. This paper explains about the privacy and security, threats, attack etc.